АНАЛІЗ ТРАКТУВАННЯ ПОНЯТТЯ “КОМПЕТЕНТНІСТЬ” У НАУКОВІЙ ЛІТЕРАТУРІ (Педагогіка вищої та середньої школи, 2007)
The article is devoted to different approaches to the category “competence”, its main characteristics, types. The own notion o f the term “competence” is considered.